2021
DOI: 10.1111/pce.14128
|View full text |Cite
|
Sign up to set email alerts
|

Changing light promotes isoflavone biosynthesis in soybean pods and enhances their resistance to mildew infection

Abstract: Mildew severely reduces soybean yield and quality, and pods are the first line of defence against pathogens. Maize-soybean intercropping (MSI) reduces mildew incidence on soybean pods; however, the mechanism remains unclear. Changing light (CL) from maize shading is the most important environmental feature in MSI. We hypothesized that CL affects isoflavone accumulation in soybean pods, affecting their disease resistance. In the present study, shading treatments were applied to soybean plants during different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…The reduction in Phe by P starvation indicates an irreversible effect of PAL genes on L-phenylalanine ammonia, as its crucial roles in plant growth and defense against various types of stresses have been reported in potato [ 73 ]. In addition, several studies have shown that light promotes catechin synthesis [ 15 ] and shade treatment is effective for the inhibition of flavonoid biosynthesis in soybean [ 29 ]. Similarly, our results support the phenomena in tea leaves whereby decreased concentrations of catechins (ECG, EGC and EGCG) were detected by half-shading under P sufficient conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in Phe by P starvation indicates an irreversible effect of PAL genes on L-phenylalanine ammonia, as its crucial roles in plant growth and defense against various types of stresses have been reported in potato [ 73 ]. In addition, several studies have shown that light promotes catechin synthesis [ 15 ] and shade treatment is effective for the inhibition of flavonoid biosynthesis in soybean [ 29 ]. Similarly, our results support the phenomena in tea leaves whereby decreased concentrations of catechins (ECG, EGC and EGCG) were detected by half-shading under P sufficient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, amino acids are responsible for tea quality. For instance, low-quality grades of black tea contain lower free amino acid contents [ 29 ]. The most abundant amino acids in tea are theanine (Thea), glutamine (Gln), glutamic acid (Glu), and arginine (Arg) [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic pathways are significantly different in soybean inoculated with Fusarium Verticillium compared to normal soybean. Flavonoid contents are significantly higher in soybean inoculated with molds, and Ja induces the synthesis of biomacromolecules such as glycine to enhance soybean resistance [ 56 ]. Moreover, mannitol, threitol and trehalose were significantly enriched in Armillaria luteobuablina -treated roots [ 57 ].…”
Section: Application Of Metabolomics In the Field Of Fungal Researchmentioning
confidence: 99%
“…As explained by the biodiversity theory, the maize-soybean intercropping system is an ecological strategy to control or relieve diseases ( Zhang et al., 2019 ). In intercropping system, soybean undergoes complex changes in light environment ( Li et al., 2021 ). During the symbiotic period of soybean and corn, soybean was in the shade.…”
Section: Introductionmentioning
confidence: 99%